A Simplified Approach for Identification of Parasitic Capacitances in Three-Phase Induction Motor Driven by PWM Inverter - Riehl, Rudolf Ribeiro [UNESP]; Covolan Ulson, Jose Alfredo [UNESP]; Andreoli, Andre Luiz [UNESP]; Alves, Alceu Ferreira [UNESP]; IEEE (Ieee, 2014)
The identification of parasitic capacitances of three-phase induction motor for studying electromagnetic interference (EMI) when it driven by PWM inverters are generally performed in laboratories by using LCR bridges. The induction motor can't be turned off in most of industrial applications, and capacitances can't be directly measured, or yet, the industry have no appropriated instrument to perform these measurements. This paper presents a simple method to determine these parasitic capacitances in induction motors up to 10 HP using characteristic equations based in referenced papers and articles. The resulting equations of this approach allowed find the induction motor's simplified equivalent circuit operating in high frequency. This approach is compared to an experimental method of parasitic capacitances determination in a 5 HP induction motor, and the results demonstrate that it is an efficient alternative to the conventional methods usually applied.
Keywords: Parasitic capacitances; Induction Motor; PWM Inverter